Incremental inverse kinematics based vision servo for autonomous robotic capture of non-cooperative space debris - Dong, Gangqi; Zhu, Z.H. (Advances in space research, 2016)
•Incremental inverse kinematics of visual servo robotic manipulator for autonomous capture of a non-cooperative target.•Integrated photogrammetry and extended Kalman filter algorithm for pose and motion estimation.•Hardware-in-the-loop simulation to validate the proposed control scheme. This paper proposed a new incremental inverse kinematics based vision servo approach for robotic manipulators to capture a non-cooperative target autonomously. The target’s pose and motion are estimated by a vision system using integrated photogrammetry and EKF algorithm. Based on the estimated pose and motion of the target, the instantaneous desired position of the end-effector is predicted by inverse kinematics and the robotic manipulator is moved incrementally from its current configuration subject to the joint speed limits. This approach effectively eliminates the multiple solutions in the inverse kinematics and increases the robustness of the control algorithm. The proposed approach is validated by a hardware-in-the-loop simulation, where the pose and motion of the non-cooperative target is estimated by a real vision system. The simulation results demonstrate the effectiveness and robustness of the proposed estimation approach for the target and the incremental control strategy for the robotic manipulator.